Efeito do extrato etanólico das folhas da Stemodia maritima Linn. e do diterpeno estemodina em modelos de hipernocicepção inflamatória aguda na articulação temporomandibular de ratos - Azevedo, José Leonaldo Miranda (2019)
Orofacial pain is described as all pain associated with soft or mineralized tissues of the oral cavity and face. It encompasses a set of conditions, among them, temporomandibular dysfunction (TMD). DTM is a set of disorders involving the masticatory muscles, temporomandibular joint (TMJ) and attached structures, representing the most prevalent category of chronic pain in the orofacial region. In the attempt to solve this pain, there are studies of substances with possible antinociceptive and anti-inflammatory activities, such as Stemodia maritima Linn (Sm) and its isolated compound esthemodine (Es). The aim of this study was to evaluate the phytotherapeutic potential of Sm and Es in the acute inflammatory hypernociception in TMJ of rats. Animals were pretreated (vo) with Sm (0.1, 1 and 10 μg / kg), Es (0.1 and 1 μg / kg) or saline 1 h prior to intra-articular formalin injection (1.5 % / 50μL), Capsaicin (1.5% / 20 μL) or saline in the left TMJ. Nociceptive behavior was assessed for 45 min. We evaluated vascular permeability through plasma extravasation of Evans Blue dye. To investigate the participation of HO-1 and NO pathway, we used the zinc inhibitors protoporphyrin IX and aminoguanidine, respectively, 30 min prior to administration of Sm or Es. To study the participation of opioid receptors, rats were pretreated with intrathecal injection of naloxone non-selective opioid inhibitor and 15min. then we administer Sm or Es. The trigeminal ganglion was removed for IL-1β dosing by ELISA in acute inflammatory hypernociception in the ATM induced by formalin. Immunohistochemistry was performed to verify the expression of TRPV-1 in the trigeminal ganglion of rats with acute inflammatory hypernociception induced by capsaicin. It was observed that pretreatment with Sm or Es reduced (p <0.05): the nociceptive response; the plasma extravasation; the expression of IL-1β and TRPV. It is also concluded that Sm and Es act as antinociceptive and anti-inflammatory agents, and that this response does not occur through the hemeoxygenase-1, nitric oxide and opioid pathways, but reduces plasma extravasation, with involvement of IL-1β and probably of TRPV-1 receptors.